Selección de un método de compensación volumétrica por calidad para el transporte por oleoducto de cuatro tipos de crudos de campos en la cuenca del Caguán-Putumayo (2017)
During the development of this degree project begins with the detailed description of the Colombian Pipeline, location, historical overview and a summary of the main physical and technical characteristics of said pipeline and later, a brief introduction was made of the generalities of volumetric compensation For quality, later the compensation methods were described: API and sulfur; Cuts by distillation and refining; Existing in the industry of the Transport of Hydrocarbons and finally reference the normativity that regulates this procedure at national and international level.